TINGKAT BODYSHAMING DI KALANGAN REMAJA BERDASARKAN GENDER - Azzahrawaani Muti'ah; Fitniwilis Fitniwilis (LPPM Institut Pendidikan Nusantara Global, 2023)
This research is motivated by a preliminary study of the field based on the results of observations and filling out questionnaires that researchers conducted on the object of class VIII students and research subjects at SMP Negeri 20 Jakarta school, where everyone does things that are considered a joke in a relationship that ends up commenting on each other and mocking both verbally and physically without realizing it becomes a normalized thing in the environment. This study aims to determine and describe how the level of bodyshaming behavior in adolescents based on gender, as well as see how big the level of bodyshaming among adolescents. The population of this study were 176 students of SMP Negeri 20 Jakarta class VIII. The sample of this study consisted of 122 samples with propotional random sampling technique. This research uses descriptive quantitative where it looks deeper, describes, explains things as they are, and draws conclusions from observable phenomena using numbers between existing variables. This research technique looks for percentages. As a way to find out how much the level of the variable is, the researcher uses parametric data analysis with the calculation of mode, median, mean, standard deviation and percentage calculation. The results obtained with a higher significance of the level of tendency of respondents in this study gender or male sex as many as 67 obtained the results of 41.70% while 55 female respondents obtained 31.91% who could answer from the total of all bodyshaming level instruments based on gender. This means that the level of bodyshaming among adolescents based on male gender is higher than female towards bodyshaming behavior